2016
DOI: 10.1038/srep33584
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of highly antibiotic resistant Bartonella bacilliformis mutants

Abstract: The objective was to develop and characterise in vitro Bartonella bacilliformis antibiotic resistant mutants. Three B. bacilliformis strains were plated 35 or 40 times with azithromycin, chloramphenicol, ciprofloxacin or rifampicin discs. Resistance-stability was assessed performing 5 serial passages without antibiotic pressure. MICs were determined with/without Phe-Arg-β-Napthylamide and artesunate. Target alterations were screened in the 23S rRNA, rplD, rplV, gyrA, gyrB, parC, parE and rpoB genes. Chloramphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…continues to be highly susceptible to antibiotics (334). Antimicrobial resistance levels have been established in a few clinical or collection isolates of B. bacilliformis (123,305,314,(335)(336)(337), and it should be taken into account that in vitro susceptibility does not consistently correlate with the in vivo outcomes for patients (330). In addition to the constitutive nalidixic acid resistance and related diminished fluoroquinolone susceptibility described previously (305,338), in a recent report 26% of isolates presented resistance to ciprofloxacin (314).…”
Section: Mechanisms Of Antimicrobial Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…continues to be highly susceptible to antibiotics (334). Antimicrobial resistance levels have been established in a few clinical or collection isolates of B. bacilliformis (123,305,314,(335)(336)(337), and it should be taken into account that in vitro susceptibility does not consistently correlate with the in vivo outcomes for patients (330). In addition to the constitutive nalidixic acid resistance and related diminished fluoroquinolone susceptibility described previously (305,338), in a recent report 26% of isolates presented resistance to ciprofloxacin (314).…”
Section: Mechanisms Of Antimicrobial Resistancementioning
confidence: 99%
“…These flagellated nonmotile variants can be bound to erythrocytes, promoting surface contact interaction. The optimal binding of bacteria to the surface of erythrocytes requires B. bacilliformis energy, most likely proton motive force-dependent motility (123,140), with the whole in vitro process taking approximately 6 h (161).…”
Section: Erythrocytes and Oroya Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…However, improper use of antibiotics has provoked massive resistance to them of many microorganisms. Such resistance to tetracycline is described for strains of Pseudomonas aeruginosa, Proteus, Staphylococcus aureus (MRSA) and Streptococcus pneumoniae [14], to chloramphenicol -for Bartonella and Staphylococcus [15], to lincomycin -for Kocuria kristinae, Sphingomonas paucimobilis, Pantoea, Staphylococcus vitulinus, Clostridium, etc. [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Though studies suggested that most of Bartonella species including B. bacilliformis are highly susceptible to mostof antibiotics, such as beta-lactams, aminoglycosides, chloramphenicol, rifampin, macrolides, tetracyclines, cotrimoxazole, fluoroquinolones[12] and gentamicin[1], but there is a potential risk of the spontaneous selection of successful antibiotic resistant B. bacilliformis clone in a clinical setting. For examples, few studies developed in vitro has showed the ability of B. bacilliformis to acquire chromosomal mutations leading to high levels of antibiotic resistance [13,14]. Lack of comprehensive analysis of B. bacilliformis genomic structure is an obstacle in developing species-specific new therapeutic compounds and vaccine candidates [5].…”
Section: Introductionmentioning
confidence: 99%